TINJAUAN HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 DALAM MENJAMIN PERLINDUNGAN HAK KONSTITUSIONAL MASYARAKAT - Yoga Siwananda; Widnyana, I Made Adi; Sugita, I Made (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Elections are an important tool in realizing democracy and popular sovereignty. However. This triggered a lawsuit to the Constitutional Court (MK) to test the constitutionality of norms that were considered contrary to the 1945 Constitution of the Republic of Indonesia. Decision Number 90/PUU-XXI/2023 which regulates the age limit of presidential and vice presidential candidates After the Constitutional Court's decision, Article 169 letter q of the Election Law was amended by adding the phrase